Impact of hydrothermal and mechanical processing on dissolution kinetics and rheology of oat β-glucan. (15th June 2017) - Grundy, Myriam M.-L.; Quint, Janina; Rieder, Anne; Ballance, Simon; Dreiss, Cécile A.; Butterworth, Peter J.; Ellis, Peter R.
Highlights: β-Glucan release from oat cell walls during incubation was not complete. Processing of oats affects the rate and extent of β-glucan release and solution rheology. The rheology of β-glucan solutions varied depending on oat composition and presence of particulates. Variations in β-glucan solubility have important implications for physiological activity. Abstract: Oat mixed-linkage β-glucan has been shown to lower fasting blood cholesterol concentrations due notably to an increase in digesta viscosity in the proximal gut. To exert its action, the polysaccharide has to be released from the food matrix and hydrated. The dissolution kinetics of β-glucan from three oat materials, varying in their structure, composition and degree of processing, was investigated by incubating the oats at 37 °C over multiple time points (up to 72 h). The samples were analysed for β-glucan content, weight-average molecular weight and rheological behaviour. Regardless of the materials studied and the processing applied, the solubilisation of β-glucan was not complete. Mechanical and hydrothermal processing led to differences in the viscosity flow curves of the recovered solutions, with the presence of particulates having a marked effect. This study revealed that the structure and processing methods applied to oat materials resulted in varied and complex rheological properties, especially when particulates are present.